(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: Comparing and analyzing the surface roughness of the CNC Novel Drilling of sisal fibre reinforced with aluminium wire mesh sandwich composite and sisal fibre composite with 45⁰ /0⁰ /45⁰ ply orientation angle. Materials and methods: The examination of surface roughness during penetrating the drill on sisal fiber metal composite overlay of sisal and aluminium wire mesh layered as sandwich (sisal - aluminium - sisal - aluminium - sisal) with sisal built up composite cover. The unidirectional sisal fiber is laid in 45°/0°/45° direction in both the overlays considered for correlation. The work material picked for this review is aluminium wire lattice of grade 6092 and unidirectional sisal fiber. The type of drill bit selected for novel drilling operation is tungsten carbide drill bit. The Sisal fibre reinforced laminates were manufactured in two groups (Experiment group =1 and Control Group =1). Sample sizes for each group were 20 with pre-test power of 80%, beta=0.05%, and CL 95%. Results:A test study is chosen with samples for every group and surface roughness is estimated for both the experimental group and control group and analyzed for its significance by SPSS software and the graphs were plotted and level of significance was found to be 0.031 (p<0.005). Conclusion: Within the limitations of the study, the experimental group of novel sisal fibre reinforced with aluminium wire mesh sandwich composite (sisal - Al - sisal - Al -sisal) with 45⁰ /0⁰ /45⁰ ply orientation angle gives the good surface finish with 26.5% improvement in surface roughness value in comparison with base materials.